Sex differences in blood pressure responses of Pekin ducks to sound stimuli and conspecific vocalizations - J.M. Schober; S. Wesley; I. Taylor; B. Ault; C. Plue; M.M. Bergman; J.R. Lucas; G.S. Fraley (Poultry Science)
We tested Pekin ducks with playbacks of 5 different vocalizations plus a no noise and white noise stimulus as our controls (N = 15 ducks/sex/treatment). The “AM long” call is a common vocalization made by both sexes. “Honk” is also produced by both sexes and is thought to be an alarm or distress call. “Pips” and “harmonics” are common vocalizations made only by hens. The “egg laying squiggle” is also only made by hens. Trials consisted of an initial recording in a quiet condition with 5 consecutive measurements of heart rate, blood pressure and respiratory rate. A specific vocalization was then played on repeat while 8 more measurements of blood pressure, heart rate and respiratory rate were taken. Finally, 5 measurements of heart rate and blood pressure were taken post playback along with a final recording of respiratory rate. Data from all blood pressure measurements (systolic, diastolic and mean arterial pressure [MAP]), heart rate (HR) and respiratory rate (RR) were subject to a principal component analysis (Proc Princomp in SAS 9.4). The significant principal components (Prin 1 loaded strongly on blood pressure and Prin 2 loaded strongly on HR and RR) were then analyzed by ANOVA with repeated measures (Proc Mixed, SAS 9.4, subject=duck ID). Our results showed there was a significant main effect of playback type on the blood pressure of ducks during the playbacks (P = 0.0276). Ducks experienced an increase in blood pressure when played back the honk vocalization, as well as the white noise control. Additionally, there was a significant interaction between sex and treatment on the after-stimulus blood pressure (P = 0.0008): after the harmonic vocalization was played, the drakes still experienced an increase in blood pressure, but the hens experienced a decrease. The drakes, but not the hens, experienced a decrease in blood pressure after the AM long vocalization was played. Our data show that there are sex differences when it comes to vocalization playbacks in Pekin ducks, but overall, the honk vocalization and white noise control significantly increased ducks’ blood pressure. This study represents a critical steppingstone toward understanding how Pekin duck vocalizations affect conspecific physiology.